(untitled) - Galbraith, John Kenneth (London, 1987)
A book explaining the history of economics; including the powerful and vested interests which moulded the theories to their financial advantage; as a means of understanding modern economics.
Keywords: Kinh tế,Economics; Lịch sử,History